Hubungan Pemberian Susu Formula Dan Makanan Pendamping ASI (MP-ASI) Dini Dengan Kejadian Diare Pada Bayi Usia 0-6 Bulan - Limois , Celine; Aidila , Diah Chairin; Halawa , Devilina; Dakhi , Bernadet Desni Irma Dewi; Fatemaluo, Aliran; Nababan, Tiarnida (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background : Infant and toddler mortality in developing countries is primarily caused by diarrhea. Formula feeding and early introduction of complementary feeding can contribute to diarrhea in infants under 6 months. Purpose : To gain knowledge about the relationship between formula feeding and early introduction of complementary feeding with the incidence of diarrhea in infants aged 0–6 months at Posyandu Balita in Helvetia Village. Methods : This research is quantitative, employing an analytic survey design and a cross-sectional approach. Out of 125 mothers with infants aged 0–6 months across all Posyandu Balita in Helvetia Village, 75 mothers were selected as samples using accidental sampling technique. Questionnaires were distributed to collect data, which was then analyzed using the chi-square test (α = 0.05). Results : There is a significant relationship between formula feeding and the incidence of diarrhea in infants aged 0–6 months, with a p-value of 0.042 (p < α). On the other hand, early MP-ASI introduction does not show a significant relationship with the incidence of diarrhea in infants aged 0–6 months, with a p-value of 0.078 (p > α). Conclusion : Mothers are encouraged to practice exclusive breastfeeding, maintain personal and baby equipment hygiene, and actively seek information about preventing diarrhea or other diseases.